Mutations in yeast Rad51 that partially bypass the requirement for Rad55 and Rad57 in DNA repair by increasing the stability of Rad51–DNA complexes - Fortin, Gary S (Nature Publishing Group, 2004)
Correction to: The EMBO Journal (2002) 21, 3160–3170. doi:10.1093/emboj/cdf293